Sociodemographic factors associated with semen quality among Malaysian men attending fertility clinic. - Muhamad, Suriyani; Sengupta, Pallav; Ramli, Roszaman; Nasir, Aslina (Wiley Online Library, 2019)
The worldwide declining trend in male fertility has been a steady concern since the past few decades. Male infertility reportedly accounts for half of the overall infertility cases in the world. Despite the evidences of reduced fertility rates in Malaysia in the recent years, there is lack of interventions regarding the reproductive parameters in Malaysian men. Complexity in determining the underlying causatives in most of the male subfertility and infertility cases limits the scope of management. The sociodemographic impacts upon overall health as well as on reproductive health of men are undeniable. The present study has analysed the data collected from patients' records in the Fertility Clinic, International Islamic University Malaysia (IIUM), from the January 2009 until December 2018. A total of 300 male patients were included in the study and were categorised according to their seminal fluid analysis (SFA) records. The sociodemographic characteristics for each subject were analysed. The results presented significant correlations among essential sociodemographic factors, such as educational attainment, marital duration as well as the age of wife, with the levels of semen abnormalities in the subjects. The study thereby unleashes scope for further investigations focusing upon the demographic factors for better insights to ameliorate male reproductive health in the Malaysian population.